3PC-061 Physicochemical stability of cloxacillin solution in polypropylene syringes at 125 mg/mL in 0.9% sodium chloride and dextrose 5% in water. (14th March 2021) - Polo, C; D'huart, E; Vigneron, J; Charmillon, A; Demore, B
Abstract : Background and importance: Cloxacillin is an antibiotic indicated in methicillin sensitive Staphylococcus aureus infections. The usual curative dosage ranges from 8 to 12 g/day, divided into 4–6 daily administrations. Continuous infusions are frequently used in the intensive care unit. The administration of concentrated solutions in an electric syringe pump would reduce the water supply and the number of daily intakes. Aim and objectives: The objective was to study the stability of cloxacillin solutions at 125 mg/mL diluted in 0.9% sodium chloride (0.9% NaCl) and in dextrose 5% in water (D5W), stored in polypropylene syringes, unprotected from light, at 20–25°C for 48 hours. Material and methods: Chemical stability was analysed by high performance liquid chromatography coupled to a photodiode array detector and by pH determination after preparation, and after storage for 6, 24 and 48 hours. The analytical method was validated according to the International Conference on Harmonisation Q2 (R1). Four syringes for each condition were prepared. Physical stability was evaluated by visual and subvisual inspection (turbidimetry by UV spectrophotometry at 350, 410 and 550 nm). Results: For each solvent, solutions at 125 mg/mL retained more than 90% of the initial concentration for 24 hours: for 0.9% NaCl (minimum 96.57%±1.69%; maximum 95.96%±1.38%) and for D5W (94.96%±1.38%; 98.08%±0.48%). After 48 hours of storage, the solutions contained <90% of cloxacillin: a minimum of 89.58%±0.43% for 0.9% NaCl and 89.47%±0.79% for D5W. During the study, pH values decreased progressively during the 48 hours of storage and pH differences were >1 pH unit after 48 hours for both solvents. During the subvisual examination, absorbance values at 410 and 550 nm increased after 48 hours. A colour change was observed at 48 hours (from colourless to very slight yellow) in 0.9% NaCl. In D5W, the solutions stained more quickly; a very slight yellow colouration was visible after 6 hours of storage which intensified after 24 and 48 hours. Conclusion and relevance: Cloxacillin solutions at 125 mg/mL in 0.9% NaCl and D5W were stable in polypropylene syringes for 24 hours at room temperature. The solutions were unstable after 48 hours of storage. References and/or acknowledgements: Conflict of interest: No conflict of interest